FREE ECONOMIC ZONES IN UZBEKISTAN: TYPES AND FAVORABLE CONDITIONS - Pardayeva Shaxrizoda (Modern American Journals, 2025)
According to the "Strategy for the Further Development of the Republic of Uzbekistan" development of the economic spheres are among the priorities. Taking into account special features of Uzbekistan 7 free economic zones have been created and 7 more will be created. Our government adopted laws to support creation of free economic zones which includes tax preferences, custom preferences and optimized administrative process for foreign and domestic investors. Based on the actuality of the above mentioned this abstract considers free economic zones in Uzbekistan.
Keywords: Free economic zones, taxes, customs, investment, foreign investors.